The Role of Catalytic Cleft and Exosite Residues of Factor VIIa for Complex Formation with Tissue Factor Pathway Inhibitor - Iakhiaev, Alexei; Ruf, Wolfram; Rao, Vijaya Mohan L. (Thrombosis and Haemostasis, 2001)
The extrinsic coagulation pathway is initiated by the binding of plasma factor VIIa (VIIa) to the cell surface receptor tissue factor (TF). Formation of the TF-VIIa complex results in allosteric activation of VIIa as well as the creation of an extended macromolecular substrate binding exosite that greatly enhances proteolytic activation of substrate factor X. The catalytic function of the TF-VIIa complex is regulated by a specific Kunitz-type inhibitor, tissue factor pathway inhibitor (TFPI). TFPI inhibition of the TF-VIIa complex was enhanced by the presence of Xa. This study investigates the relative contribution of catalytic cleft and exosite residues in VIIa for inhibitory complex formation with TFPI. VIIa protease domain residues Q176, T239 and E296 are involved in the formation of stable inhibitor complex with free TFPI. Kinetic analysis further demonstrated a predominant role of the S2’ subsite residue Q176 for the initial complex formation with TFPI. In contrast, no significant reductions in inhibition by TFPI-Xa were found for each of the mutants in complex with phospholipid reconstituted TF. However, reduced rates of inhibition of the VIIa Gla-domain (R36) and Q176 mutant by TFPI-Xa were evident when TF was solubilized by detergent micelles. These data demonstrate docking of the TFPI-Xa complex with the macromolecular substrate exosite and the catalytic cleft, in particular the S2’ subsite. The masking of the mutational effect by the presence of phospholipid shows a critical importance of Xa Gla-domain interactions in stabilizing the quaternary TF-VIIa-Xa-TFPI complex.
Keywords: Factor VIIa; tissue factor pathway inhibitor; tissue factor; factor Xa; protein interaction